1998
DOI: 10.1097/00007691-199808000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metabolic Inhibitors on Cyclosporine Pharmacokinetics Using a Population Approach

Abstract: Drugs known to inhibit the metabolism of cyclosporine are administered concomitantly to those who undergo cardiothoracic transplantation. The aim of this study was to examine in quantitative terms the relationship between cyclosporine oral dose rate and the trough concentration (Css(trough)) at steady state in patients who undergo cardiothoracic transplantation and are administered cyclosporine alone or in combination with drugs known to inhibit its metabolism. Dose and whole blood cyclosporine Css(trough) obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Eight patients received a 24-h infusion of 5 mg/kg of CsA, followed by a second 24-h infusion of 5 mg/kg of CsA (with ketoconazole 200 mg given by feeding tube, to increase the bioavailability of the CsA), after a washout period of 24 h. The rationale for the administration of ketoconazole, an antifungal agent, is because CsA undergoes significant metabolism mediated by cytochrome P4503A4 (CYP3A4) isozyme and P glycoprotein (PgP) efflux in the gut wall, liver, and blood-brain barrier (Lown et al, 1997), with significantly reduced oral bioavailability. Several investigators have, therefore, used inhibitors of CYP3A4 and/or PgP, such as ketoconazole, to improve bioavailability of the drug and decrease the cost of therapy (McLachlan and Tett, 1998;Foradori et al, 1998;Jones, 1997). Since a high brain concentration of CsA was an aim of our study, ketoconazole seemed to be a rational addition to our trial design.…”
Section: Cyclosporin a Administrationmentioning
confidence: 99%
“…Eight patients received a 24-h infusion of 5 mg/kg of CsA, followed by a second 24-h infusion of 5 mg/kg of CsA (with ketoconazole 200 mg given by feeding tube, to increase the bioavailability of the CsA), after a washout period of 24 h. The rationale for the administration of ketoconazole, an antifungal agent, is because CsA undergoes significant metabolism mediated by cytochrome P4503A4 (CYP3A4) isozyme and P glycoprotein (PgP) efflux in the gut wall, liver, and blood-brain barrier (Lown et al, 1997), with significantly reduced oral bioavailability. Several investigators have, therefore, used inhibitors of CYP3A4 and/or PgP, such as ketoconazole, to improve bioavailability of the drug and decrease the cost of therapy (McLachlan and Tett, 1998;Foradori et al, 1998;Jones, 1997). Since a high brain concentration of CsA was an aim of our study, ketoconazole seemed to be a rational addition to our trial design.…”
Section: Cyclosporin a Administrationmentioning
confidence: 99%
“…Coadministration of valproic acid and more than 1 enzyme‐inducer, for example, typically results in a greater decrease in valproic acid concentrations. McLachlan and Tett 63 similarly found that treatment with 2 CYP3A4 inhibitors (ie, ketoconazole and diltiazem) inhibited the dose‐rate‐ C ss trough ratio of cyclosporine, a CYP3A4 substrate, more potently than did treatment with 1 inhibitor (eg, ketoconazole) alone (84.1% vs 76.9%, respectively).…”
Section: Population‐based Methods Of Evaluating Drug‐drug Interactionsmentioning
confidence: 97%
“…Several of the studies listed in Table III revealed additional unique characteristics of the population‐based approach. For example, McLachlan and Tett 63 evaluated the impact of different CYP3A4 inhibitors on dose‐rate‐ C ss trough ratio for cyclosporine using the population‐based approach. These researchers identified a rank order of interactions in which ketoconazole plus diltiazem inhibited the dose‐rate‐ C ss trough ratio most potently, followed by ketoconazole alone, itraconazole alone, and diltiazem alone.…”
Section: Population‐based Methods Of Evaluating Drug‐drug Interactionsmentioning
confidence: 99%
“…Itraconazole and diltiazem have subsequently been shown to be effective for cyclosporine dose-sparing as well. Florea et al [8] reported a 48% decrease in the total daily dose of cyclosporine when administered with itraconazole while another study found that cyclosporine dose could be reduced by 23%, 40%, 75% and 80% when combined with diltiazem, itraconazole, ketoconazole or ketoconazole plus diltiazem, respectively [9]. Gerntholtz et al [5] reported an 85% reduction in cyclosporine dose with ketoconazole and suggested that this combination was critical in making transplantation more affordable in developing countries.…”
Section: Boosted Regimens For Treating Hiv Infectionmentioning
confidence: 99%